Acid Modified Diatomaceous Earth - A Sorbent Material for Thin Layer Chromatography - Ergül, S.; Savaşçi, Ş. (Preston Publications, 2008)
Natural diatomaceous earth (DE) is modified by flux calcination and refluxing with acid. To characterize natural DE, modified DE's [flux calcinated (FC)DE and FCDE-I] and silica gel 60GF254 (Si-60GF254) are analyzed microscopically, physically, and chemically by various techniques. FCDE-I and Si-60GF254 are investigated for their usefulness in the stationary phase of thin layer chromatography (TLC) both individually and in composition. Sodium diethyldithiocarbamate (DEDTC) and ammonium pyrrolidinedithiocarbamate (PyDTC) are prepared as Co or Cu (M) complexes [M(DEDTC)2 and M(PyDTC)2, respectively]. These complexes and their mixtures are run on thin layers of Si-60GF254 and FCDE-I individually, and on various FCDE-I and Si-60GF254 mixtures. Pure toluene and various toluene-cyclohexane mixtures (3:1, 1:1, 1:2, 1:3, v/v) are used as mobile phases for the running the complexes. The best analytical separations of both M(DEDTC)2 and M(PyDTC)2 complexes are obtained when using pure toluene and toluene-cyclohexane (3:1, 1:1, v/v) as mobile phases on FCDEI-Si-60GF254 (1:3, 1:1, w/w) layers as stationary phases. This study shows that it is possible to qualitatively analyze and to satisfactorily separate a mixture Cu2+ and Co2+ cations on cited chromatographic systems.